2016
DOI: 10.1038/srep21483
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 promotes tumor invasion in colorectal cancer via the CK1ε/Dvl2 axis

Abstract: DDX3, a subunit of CK1ε, phosphorylates Dvl2 to promote β-catenin activation. Overexpression of the Dvl2 protein results in potent activation of β-catenin/TCF signaling in colorectal cancer. Therefore, we hypothesized that DDX3 might promote tumor invasion via the CK1ε/Dvl2 axis due to β-catenin/TCF activation. Western blotting showed that β-catenin expression was decreased by DDX3 knockdown and increased by DDX3 overexpression in colorectal cancer cells. The TCF promoter activity and invasion capability were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…In contrast, several groups obtain different conclusions of the role of DDX3 in colorectal cancer (37)(38)(39)(40). In KRAS-mutated colon cancer cells, DDX3 promotes cell invasion and the nodule formation of xenograft lung tumor due to β-catenin/TCF activation through the CK1ε/Dvl2 axis (37). In addition, DDX3 enhances KRAS transcription and activates the following β-catenin/ZEB1 signaling to promote KRAS-mediated tumor invasion (38).…”
Section: Ddx3 Role In Cancer: Tumor Suppressor or Oncogenementioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, several groups obtain different conclusions of the role of DDX3 in colorectal cancer (37)(38)(39)(40). In KRAS-mutated colon cancer cells, DDX3 promotes cell invasion and the nodule formation of xenograft lung tumor due to β-catenin/TCF activation through the CK1ε/Dvl2 axis (37). In addition, DDX3 enhances KRAS transcription and activates the following β-catenin/ZEB1 signaling to promote KRAS-mediated tumor invasion (38).…”
Section: Ddx3 Role In Cancer: Tumor Suppressor or Oncogenementioning
confidence: 99%
“…Inhibition of DDX3 by a small inhibitor RK-33 reduces cell proliferation and causes a G1 arrest in colorectal cancer cells (40). In addition, a high DDX3 expression leads to poor clinical overall survival (OS) for colorectal cancer patients (37)(38)(39)(40).…”
Section: Ddx3 Role In Cancer: Tumor Suppressor or Oncogenementioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that DDX3 promoted tumor invasion in colorectal cancer, regardless of APC loss, by activating β-catenin/TCF signaling via the CK1ε/Dvl2 axis 10. We further demonstrated that DDX3 upregulated KRAS transcription and enhanced oncogenic KRAS-mediated tumor invasion following β-catenin/TCF activation by MEK/ERK and PI3K/AKT signaling 11.…”
Section: Introductionmentioning
confidence: 74%